The EASTR Study: indications for transfusion and estimates of transfusion recipient numbers in hospitals supplied by the National Blood Service. - Wells, A; Llewelyn, C; Casbard, A; Johnson, A; Amin, M; Ballard, S; Buck, J; Malfroy, M; Murphy, M; Williamson, L (2009)
This study provides data on National Blood Service (NBS) red blood cell (RBC, n = 9142), platelet (PLT, n = 4232) and fresh frozen plasma (FFP, n = 3584) recipients independently sampled by monthly quota from 29 representative hospitals over 12 months in 2001-2002. Hospitals were stratified by size according to total yearly RBC issues. Transfusion indications were chosen from diagnostic and procedural codes, and recipients grouped into Epidemiology and Survival of Transfusion Recipients Case-mix Groups (E-CMGs). The main E-CMGs were digestive [19% of RBC recipients; including 5% gastrointestinal (GI) bleeds and 3% colorectal surgery], musculoskeletal (15%; 12% hip and knee replacement), haematology (13%) and obstetrics and gynaecology (10%). Renal failure, fractured neck of femur, cardiac artery by-pass grafting (CABG) and paediatrics, each accounted for 3-4% recipients. FFP recipients: the main E-CMGs were digestive (21% of FFP recipients; including 7% GI bleeds and 3% colorectal surgery), hepatobiliary (15%; 7% liver disease and 2% liver transplant), cardiac (12%) and paediatrics (9%) The renal, paediatrics, vascular and haematology E-CMGs each had 6-7% of recipients. PLT recipients: the main E-CMGs were haematology (27% of PLT recipients; including 9% lymphoma and 8% acute leukaemia), cardiac (17%), paediatrics (13%), hepatobiliary (10%) and digestive (9%). Back-weighting gave national estimates of 433 000 RBC, 57 500 FFP and 41 500 PLT recipients/year in England and North Wales, median age 69, 64 and 59 years, respectively. Digestive and hepatobiliary indications emerged as the top reason for transfusion in RBC and FFP recipients, and was also a frequent indication in PLT recipients.